Implementation of the Liverpool Care Pathway (LCP) for the Dying Patient in the Inpatient Hospice Setting: Development and Preliminary Assessment of the Italian LCP Program. (February 2014) - Leo, Silvia Di; Bono, Laura; Romoli, Vittoria; West, Emily; Ambrosio, Raffaella; Gallucci, Michele; Pilastri, Paola; Ciura, Pietro La; Morino, Piero; Piazza, Massimo; Valenti, Danila; Franceschini, Catia; et al.
Background: The Liverpool Care Pathway (LCP) is extensively used in hospices, but the literature on the process of implementation is scarce. Aim: Developing, piloting, and preliminarily assessing the LCP program within the inpatient hospice setting. Methods: This is a phase 0-1 study, according to the Medical Research Council (MRC) Framework, divided into three phases: literature review on LCP in hospice and development of the Italian version of the LCP program (LCP-I), development of a procedure for assessing the quality of the implementation process and assessing the feasibility of the implementation process, and piloting the procedure in 7 inpatient Italian hospices. Results: The LCP was implemented in all the hospices involved. A high proportion of physicians (50%-100%) and nurses (94%-100%) attended the self-education program. The self-implementation of the LCP-I program was completed in all hospices. The proportion of patients who died on LCP-I ranged between 35.6% and 89.1%. Professionals from 2 hospices reported a positive impact of the LCP-I. Conversely, professionals from 2 hospices did not recognize a positive impact of the program and did not agree to maintain the LCP-I in hospice. Finally, professionals from the other 3 hospices reported intermediate evaluations (1 stopped to use the LCP-I). Some weaknesses emerged from the external audits, related to the self-education and the self-implementation approach. Professionals required an external support from a trained palliative care team with reference to both phases. Conclusions: The LCP-I implementation within hospices is feasible, and the process of implementation is evaluable. Issues that occurred within the implementation process suggest the introduction of an external support from a trained palliative care team in implementing the LCP program.